2010
DOI: 10.1002/ange.201005347
|View full text |Cite
|
Sign up to set email alerts
|

N‐Phosphinyl Phosphoramide—A Chiral Brønsted Acid Motif for the Direct Asymmetric N,O‐Acetalization of Aldehydes

Abstract: Feineinstellung der Positionen: Das einfach zugängliche N‐Phosphinylphosphoramid 1 erwies sich als hoch effizienter und enantioselektiver Katalysator der Titelreaktion. Der präparative Nutzen dieses Vorgehens wurde mit der ersten katalytischen asymmetrischen Synthese des Analgetikums (R)‐Chlorothenoxazin bewiesen (siehe Schema).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 45 publications
0
7
0
1
Order By: Relevance
“…Although phosphoric acids were successful in enantioselective synthesis of N,N-aminals, they failed in promoting direct N,O-acetalization between 2-hydroxybenzamide 84 and aldehydes 25 with good enantioselectivity.I ndeed, the reactionr equired the use of N-phosphinyl phosphoramide NPA2 to pro-ceed efficiently (Scheme 19). [51] The authors rationalized these results by ah igherr igidity of the chiral cavity.T his originalr eaction became ar eal synthetic tool since it was appliedt ot he synthesis of analgesic (R)-chlorothenoxazine 85 a.T he target was obtained in 80 %y ield but with ad isappointing7 2% ee. Nonetheless, the enantiopurity was improved to be 93 % ee due to the recrystallization step.…”
Section: C-x Bond Formations By Enantioselective Nucleophilic Additiomentioning
confidence: 94%
“…Although phosphoric acids were successful in enantioselective synthesis of N,N-aminals, they failed in promoting direct N,O-acetalization between 2-hydroxybenzamide 84 and aldehydes 25 with good enantioselectivity.I ndeed, the reactionr equired the use of N-phosphinyl phosphoramide NPA2 to pro-ceed efficiently (Scheme 19). [51] The authors rationalized these results by ah igherr igidity of the chiral cavity.T his originalr eaction became ar eal synthetic tool since it was appliedt ot he synthesis of analgesic (R)-chlorothenoxazine 85 a.T he target was obtained in 80 %y ield but with ad isappointing7 2% ee. Nonetheless, the enantiopurity was improved to be 93 % ee due to the recrystallization step.…”
Section: C-x Bond Formations By Enantioselective Nucleophilic Additiomentioning
confidence: 94%
“…There are various reaction systems reported for the synthesis of hemiaminals, such as dicyclohexylboron chloride‐triethylamine system for coupling of amide and aldehyde, polyvalent iodine reagent oxidation systems, phosphoric acid catalysed addition of alcohol to N‐acyl imines, the Pd‐catalysed C−N coupling reaction, titanium ethoxide catalyzed coupling of amide and aldehyde, et al ,. Among those methodologies, nucleophilic addition of alkoxyl group to the imine is one of the typical methods for the synthesis of hemiaminals ,, ,…”
Section: Figurementioning
confidence: 99%
“…Noteworthy examples are Povarov reactions, O-alkylations, Pictet-Spengler reactions or benzidine rearrangement [73][74][75][76]. Chiral BA have shown particularly successful performances in the acetalisation reaction [77][78][79]. In 2005, Antilla et al reported about the amidation of imines, which consists of a N,N-acetalisation.…”
Section: Brønsted Acid Catalysismentioning
confidence: 99%